PETA SIKAP PEMILIH PEMULA DI YOGYAKARTA TAHUN 2014 - Sartana Sartana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2014)
This research aims to know the response of beginning vooter in Togyakarta. This research used mixed approached; Quantitative and Qualitative methodology, there are 712 respondence, there are 712 respondent (352 male and 360 female) engage in this research. The data collected by quesioner and interview. Quantitative data analyzed by descriptive analysis, and qualitative data analyzed by content analysis. The result of this research shows that the majority of beginning vooter are have enthusism in participating general election. But they are tend tobe pasive. They are lazy to searching information which related to general election and rarely engage in caimpign. This respond rised because they view that the result of general election before are the leaders who is corrupt. The beginning vooter considering leader who is have integrity and the riil problems in the society. And that ideal leader they can find in the middle class. Activist and proffesionals. Generally this reserach show that begnning vooter tend tobe emosional vooter because they have limited information relating with the chandidate.